2013
DOI: 10.4049/jimmunol.1202860
|View full text |Cite
|
Sign up to set email alerts
|

Human Fc Receptor–Like 5 Binds Intact IgG via Mechanisms Distinct from Those of Fc Receptors

Abstract: Fc receptor-like 5 (FCRL5) regulates BCR signaling and has been reported to bind aggregated IgG. Using surface plasmon resonance, we analyzed the interaction of native IgG samples with FCRL5, revealing a complex binding mechanism, where isotype is just one factor. FCRL5 bound IgG1 and IgG4 with approximately 1 μM KD, while the interaction with IgG3 was a magnitude weaker. However, IgG2 samples displayed a wide range of affinities, indicating that additional factors affect binding. We used a panel of 19 anti-FC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 45 publications
3
59
0
Order By: Relevance
“…Human B cells are known to express two FcγRs for IgG, FcγRIIb and FcRL55622. To determine if these receptors could contribute to the interaction of hexa-Fc with B cells, and to overcome issues of background binding observed with isolated B cells, we evaluated the extent of binding of hexa-Fc to 293 cells transiently expressing these proteins or control CD200R and FcRL4 receptors by FACS6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human B cells are known to express two FcγRs for IgG, FcγRIIb and FcRL55622. To determine if these receptors could contribute to the interaction of hexa-Fc with B cells, and to overcome issues of background binding observed with isolated B cells, we evaluated the extent of binding of hexa-Fc to 293 cells transiently expressing these proteins or control CD200R and FcRL4 receptors by FACS6.…”
Section: Resultsmentioning
confidence: 99%
“…Since the interaction of IVIG with FcRL522, FcγRIIb28 and DC-SIGN91129 has been attributed to direct and/or indirect effects of sialic acid on the Fc, we next investigated the nature of the N -glycans on hexa-Fc and compared them with two different IVIG preparations (GammaGard™ or Malawian IVIG) and the dimeric-Fc (Figure 4). MS analysis of hexa-Fc revealed a paucity of sialylated structures but enrichment for high mannose glycans (Man 5 GlcNAc 2 , Man 6 GlcNAc 2 ) (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with recent publications. 45,46 Interestingly, oligomannose-sensitive binding of FcRL5 has not been previously observed.…”
Section: Multiplexed Prediction Of Equilibrium Binding Affinitymentioning
confidence: 89%
“…Using a chimeric receptor containing the cytoplasmic tail of FCRL5, crosslinking FCRL5 and the BCR was shown to recruit SHP-1 to the two ITIM motifs of FCRL5, resulting in reduced BCR-induced calcium mobilization and protein tyrosine phos-phorylation (20). We and others reported that FCRL5 binds intact IgG via a complex mechanism (21,22), and therefore immune complexes may link FCRL5 to the BCR, potentially blocking B cell activation similarly to the inhibitory FcgRIIB. Potential activating functions were also proposed for FCRL5 (23), similarly to FCRL3 (24) and FCRL4 (25), suggesting dual regulatory capacities.…”
Section: T He Generation Of B Cell Memory Is An Important Component Omentioning
confidence: 93%